If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -5n + 2n Combine like terms: -5n + 2n = -3n 0 = -3n Solving 0 = -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 0 + 3n = -3n + 3n Remove the zero: 3n = -3n + 3n Combine like terms: -3n + 3n = 0 3n = 0 Divide each side by '3'. n = 0 Simplifying n = 0
| 15(2+x)-3X=114 | | (3x+4)+15=9 | | 100=20-5r | | 3-4x=18-x | | -5-14=-3x+2 | | 1.2x+0.3=7.5 | | 1/3(9x+27)-4=1/2(2x+54) | | 5c+30= | | 4.5+2p=8.7 | | 6(3-x)=42 | | 4(1+x)=-12 | | 10x-15=17-4x | | 4(t-5)=2t | | 6a-5=a+15 | | x-y=62 | | 2=4(z+1) | | a+4b=-2 | | 23-4x=-7x+2 | | 6c-8=2c | | 3x+17=5x-13 | | 0.2b=10 | | 3x-7=x+29 | | 3y+8=x | | 2n+15=3n | | 5t-1=6-5 | | -3x+21x= | | 3s=45 | | 8.5x+19.51=-11.5x+18.81 | | 10x-72=12x | | 10x-72=10x | | -3(t-6)-(t+4)=3 | | 2x-5=155 |